2012
DOI: 10.33899/edusj.2012.58994
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some Trace Elements and Biochemical Parameters on Breast Cancer

Abstract: Influence of some Trace Elements and Biochemical Parameters on Breast … 35The study investigates the levels of serum trace elements as well as total protein and cholesterol which may be regarded as biochemical markers in the case of breast cancer. Serum samples were collected from 25 healthy females and 25 females with breast cancer, 24 hours before mastectomy surgery. Serum Cu, Zn, Pb and Fe were measured by using the atomic absorption spectrophotometer. Total protein, total cholesterol and HDL-cholesterol we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(46 reference statements)
1
1
1
Order By: Relevance
“…This study agrees with Seema and his group (22) and Fagherazzi et al (23), where a significant decrease in the level of total cholesterol was observed in breast cancer patients compared to the control group due to its increased use by tumor cells to build a new biofilm. The present results do not agree with Al-Faraji ( 24), Mahmoud et al (25), Al-Rabee et al (26), Wehbe et al (27), and Alacacioglu et al (28), where a significant increase was observed in the level of cholesterol in women with breast cancer and this it may be due to metabolism and increased fat oxidation, which may be associated with cancers because it has an important role in maintaining cell integrity. The cholesterol formation pathway may also produce different tumor compounds.…”
Section: Resultscontrasting
confidence: 87%
“…This study agrees with Seema and his group (22) and Fagherazzi et al (23), where a significant decrease in the level of total cholesterol was observed in breast cancer patients compared to the control group due to its increased use by tumor cells to build a new biofilm. The present results do not agree with Al-Faraji ( 24), Mahmoud et al (25), Al-Rabee et al (26), Wehbe et al (27), and Alacacioglu et al (28), where a significant increase was observed in the level of cholesterol in women with breast cancer and this it may be due to metabolism and increased fat oxidation, which may be associated with cancers because it has an important role in maintaining cell integrity. The cholesterol formation pathway may also produce different tumor compounds.…”
Section: Resultscontrasting
confidence: 87%
“…In addition, it is considered as measure of the susceptibility or progression of a range of neurological, developmental and metabolic disorders, including diabetes and cardiovascular disease, it also linked to CD . The value of Cu/Zn mean ratio observed in our study was increased for the global population in the plasma of cancer patients compared to healthy control according to Mahmood et al…”
Section: Resultssupporting
confidence: 63%
“…Similar to our findings, in study carried by Mahmood AA, et al, the women with breast cancer exhibited a significant increase in the level of serum Cu as compared to the controls (P < 0.009). On the other hand, serum Zn level was significantly lower in the breast cancer group (P < 0.002) than in the control [21].…”
Section: Discussionmentioning
confidence: 73%